Syafiq targets gold in HK after shedding the pounds - The Star (2012)
KUALA LUMPUR: Cycling enthusiast Mohd Syafiq Ridhwan has shed the pounds and is ready to wreck havoc when the Asian Bowling Champion ships begin from sept 2-11 in hong Kong.